2015
DOI: 10.1007/s10853-014-8796-9
|View full text |Cite
|
Sign up to set email alerts
|

Release of copper complexes from a nanostructured sol–gel titania for cancer treatment

Abstract: Copper complexes containing inorganic ligands were loaded on a functionalized titania (F-TiO 2 ) to obtain drug delivery systems. The as-received copper complexes and those released from titania were tested as toxic agents on different cancer cell lines. The sol-gel method was used for the synthesis and surface functionalization of the titania, as well as for loading the copper complexes, all in a single step. The resultant Cu/F-TiO 2 materials were characterized by several techniques. An ''in vitro'' releasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It was found that independently of the copper complex and also the cell line used, low concentrations of each copper compound were sufficient to kill almost 100 % of cancer cells. Both copper complexes alone as well as those loaded on TiO2 had higher toxic effect than cisplatin [193].…”
Section: New Perspectives: Drug Delivery Systems For Administering Anmentioning
confidence: 93%
“…It was found that independently of the copper complex and also the cell line used, low concentrations of each copper compound were sufficient to kill almost 100 % of cancer cells. Both copper complexes alone as well as those loaded on TiO2 had higher toxic effect than cisplatin [193].…”
Section: New Perspectives: Drug Delivery Systems For Administering Anmentioning
confidence: 93%
“…The semiconductors such as ZnS, CdSe, InP, Cds, TiO 2 , ZnO, CuO, PbS and Si are exploited for their antibacterial property [10][11][12][13][14]. Of so many semiconductors available, TiO 2 is very often preferred for clinical applications such as to impede bacterial resistance to prevent infections in surgical wounds and burnt patients [15,16]. Different forms of titania such as 1D nanotubes, 2D thin films, etc., have been studied for their antibacterial properties [17][18][19].…”
Section: Aeromonas Salmonicida Escherichia Coli Staphylococcus Aureusmentioning
confidence: 99%
“…Photocatalysis is a green technology with important applications in the fields of energy and the environment. [2] As one of the key parts of photocatalytic technology, titanium dioxide (TiO 2 ) photocatalyst is generally applied in sewage treatment, photoelectrolysis of water and photodynamic therapy owing to its low cost, high stability and strong oxidation ability. [3][4][5][6] While the wide band gap (about 3.2 eV) and fast electron and hole coupling rate of TiO 2 limit its application in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%